1999
DOI: 10.1021/jm960682u
|View full text |Cite
|
Sign up to set email alerts
|

N-Substituted Adenosines as Novel Neuroprotective A1 Agonists with Diminished Hypotensive Effects

Abstract: The synthesis and pharmacological profile of a series of neuroprotective adenosine agonists are described. Novel A(1) agonists with potent central nervous system effects and diminished influence on the cardiovascular system are reported and compared to selected reference adenosine agonists. The novel compounds featured are derived structurally from two key lead structures: 2-chloro-N-(1-phenoxy-2-propyl)adenosine (NNC 21-0041, 9) and 2-chloro-N-(1-piperidinyl)adenosine (NNC 90-1515, 4). The agonists are charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 69 publications
4
58
0
Order By: Relevance
“…ADAC, an A 1 AR agonist, was potent in cerebroprotection in a model of global ischaemia in gerbils 134 . The A 1 AR agonist NNC-21-0136 was neuroprotective in both global and focal rodent ischaemia models and had diminished cardiovascular effects in rats compared with reference A 1 AR agonists, such as CPA 135 . However, it was recently shown that deletion of the gene that encodes the A 1 AR does not alter neuronal damage that occurs after ischaemia in vivo or in vitro 136 , although A 1 ARs have been shown to be relevant to hypoxia protection in newborn mice 137 .…”
Section: Ischaemia and Neuroprotectionmentioning
confidence: 93%
“…ADAC, an A 1 AR agonist, was potent in cerebroprotection in a model of global ischaemia in gerbils 134 . The A 1 AR agonist NNC-21-0136 was neuroprotective in both global and focal rodent ischaemia models and had diminished cardiovascular effects in rats compared with reference A 1 AR agonists, such as CPA 135 . However, it was recently shown that deletion of the gene that encodes the A 1 AR does not alter neuronal damage that occurs after ischaemia in vivo or in vitro 136 , although A 1 ARs have been shown to be relevant to hypoxia protection in newborn mice 137 .…”
Section: Ischaemia and Neuroprotectionmentioning
confidence: 93%
“…Branching of the alkyl groups in N 6 -substituted adenosines has been well studied at the A 1 AR and A 2A AR. [13][14][15][16] At the hA 3 AR, a moderate degree of stereoselectivity of binding was observed for introduction of a methyl group in the R configuration at either the 1-(28 compared with 29) or 2-(30 compared with 31) position.…”
Section: Biological Activitymentioning
confidence: 99%
“…One of the analogues, containing a 3-nitro group (15), was resolved into pure diastereomers with HPLC, using the chiral column Chiralpak AD. The assignment of absolute configuration was done by analogy to the unsubstituted phenylcyclopropyl derivatives as standards.…”
Section: Introductionmentioning
confidence: 99%
“…The selective modulation of A1AR may also have neuroprotective effects as adenosine can counteract the toxic effects of glutamate-mediated excitotoxicity (141). Indeed, several A1AR agonists display neuroprotective properties in animal models of cerebral ischemia (142,143,144). In addition, stimulation of A3AR is also neuroprotective in a gerbil model of ischemia (145).…”
mentioning
confidence: 99%